Ein geniales Gewebe (Deutsche Heilpraktiker-Zeitschrift, 2015)
Ein Gespräch mit Dr. Robert Schleip.
Keywords: Interview; Faszien; Fasziengewebe; Faszienforschung; Rolfing; Faszientherapie; Medau-Gymnastik; Tractus iliotibialis; Meridiane; Ruffini-Rezeptoren; Pacini-Rezeptoren; Interozeptoren